LINGKUNGAN DAERAH ENDEMIS LEPTOSPIROSIS DESA SUMBERSARI, KECAMATAN MOYUDAN, KABUPATEN SLEMAN PROPINSI DAERAH ISTIMEWA YOGYAKARTA - , Maria Agustini ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Leptospirosis is one of zoonosis disease which their transmission is through environment, both biotic, abiotic environment and social environment such as human behavior. In Sumbersari Village, Moyudan Subdistrict, Sleman Regency, Yogyakarta Special Region (DIY), leptospirosis was found since 2007. The number of case in 2008 and 2009 was reported 1 for each, but in 2010 increased to 40 cases with 1 mortality. Objectives: To describe the abiotic, biotic and human behavior factors condition that can support transmission incidence of leptospirosis in endemic leptospirosis area in Sumbersari Village, Moyudan Subdistrict, Sleman Regency, Yogyakarta Special Region (DIY). Methods: The study was observational descriptive study with cross sectional design. Population in this study was population in Sumbersari Village, Moyudan Subdistrict, Sleman Regency, DIY. The subject of the study were leptospirosis cases and communities surrounding who meet inclusion criteria. Results: Biotic environment: the number of caught mouse were 45. The kind of rat that were found indoor are Rattus tanezumi was 62.22% and Suncus murinus was 31.11%, outdoor Suncus Murinus was 6.67%. The result from laboratory test for Leptospira sp bacteria on sample in the environment was negative (was not found Leptospira sp). The most of vegetation was agricultural plant (rice) with continual through the year. Water and soil pH in the environment was in range 6.47â7.29. with air temperature 250C â 270C, air humidity 78% - 85%. Rainfall intensity was 115mm â 525 mm. Factors influenced to the leptospirosis transmitted are: 1. Community activities in the river /rice fields, 2. Washing part of the the body without soap after working in the rice field / river, 3. Poor sanitation environment, 4. Air ventilation and wall condition which enabling rat to enter the house.